Feasibility of Validation Results of Multimodality Picture Story Book Development with Educational Game Approach in Language Learning - Caecilia Fani Sulistyaningrum; Yuliana Setyaningsih; Galih Kusumo (Jurnal Pembelajaran Bahasa dan Sastra, 2025)
This research is motivated by the low interest in reading among early childhood children, the use of less engaging learning media, and the dominance of conventional storybooks that only display static text and images without considering children's diverse learning styles. This study aims to determine the feasibility of validating the development of multimodality-based picture storybooks with an educational game approach in early childhood language learning. This research uses a quantitative descriptive design. From the perspective of data sources, this study uses a library method. Data on multimodality-based picture storybooks with an educational game approach in early childhood language learning were collected using observation guidelines, instruments assisted by checklists. Validation was carried out by each of a material expert, a media expert, and an early childhood education practitioner on eight aspects of feasibility, namely material content, multimodality, language, educational games, visual appearance, accessibility, local cultural integration, and holistic aspects. The validation results showed a total score of 90 out of a maximum score of 96, which, after being converted to 94%, is included in the very valid category or can be used without revision. Thus, this multimodality-based picture story book with an educational game approach in early childhood language learning is declared very suitable for use in language learning for children aged 5-6 years in PAUD because it fulfills the elements of content, visual, educational, and cultural contextual suitability, and children's development needs.